“Niveles de abonamiento orgánico en el cultivo de lechuga (lactuca sativa L.), variedad great lakes, en suelos ultisoles de la banda de shilcayo-San Martín-Perú” - García Flores, Wilter (2006)
The present work was developed in the Found Miraflores in the year 2 006, Sector Ahuashiyacu district of the Band of Shilcayo, county of San Martín and Region San Martín, in a floor with characteristics that next is described: texture, sandy Franco; pH, 5,7; match available 7,0 ppm; changeable potassium, O, 19 meq. /100 g of floor. The objective of this work was to evaluate the application of different dosages of Humus, looking for which of these, it is the good dose for the yield of the lettuce (var.: Great Lake). Different parameters were evaluated like: Height of plants, number of leaves, size of roots, production and longitude of leaves as much the long one as the width. The used design was that of Complete Blocks Randomizados with 5 treatments and 4 repetitions, the dosages were the following ones: TO (Absolute Witness), T1 (HUMUS = 1,25 Kg. /1 m2), T2 (HUMUS = 1,37 Kg. /1 m2), T3 (HUMUS = 1,50 Kg. /1 m2) and T 4 (HUMUS = 1,68 Kg. /1 m2), the distancing was of 0,25 between lines and 0,35 among plants. The results determine that the T2 (HUMUS = 1,37 Kg. /1 m2) it was the but excellent in the yield, the same as in the relationship cost/benefit, with 17 497,50 Kg. I there is and 20,81 o/o (C/B) respectively, in front of the TO (Witness) with 10350,00 Kg. I there is (yield) and 32,49% (C/B).